Devising chemically robust and cationic Ni(II)-MOF with nitrogen-rich micropores for moisture-tolerant CO2 capture: highly regenerative and ultrafast colorimetric sensor for TNP and multiple Oxo-anions in water with theoretical revelation - Goswami, Ranadip; Seal, Nilanjan; Dash, Soumya Ranjan; Tyagi, Anshu; Neogi, Subhadip (ACS Applied Materials & Interfaces, 2019)
Metal-organic frameworks (MOFs) show distinctive superiority for carbon dioxide (CO2) capture and luminescent sensing of toxic pollutants over other materials where combination of both of these properties together with improvement of hydrolytic stability and pore functionality is critical to environmental remediation applications. The Ni(II) framework [Ni-2(mu 2OH)(azdc)(tpim)](NO3)center dot 6DMA center dot 6MeOH (CSMCRI-3) (tpim = 44'4(2)-(1H-imidazole-245-triyl)tripyridine H(2)azdc = azobenzene-44'-dicarboxylic acid DMA = dimethylacetamide CSMCRI = Central Salt & Marine Chemicals Research Institute) encompassing cationic [Ni-2(mu(2)-OH)(CO2)(2)] SBUs is solvothermally synthesized from nitrogen-rich and highly fluorescent organic struts. The noninterpenetrated structure containing free nitrogen atom affixed microporous channels is stable in diverse organic solvents and weakly basic and acidic aqueous solutions. The activated MOF (3a) exhibits strong CO2-framework interaction and extremely selective CO2 adsorption over N-2 (292.5) and CH4 (11.7). Importantly water vapor exposure does not affect the surface area and/or multiple CO2 uptake-release cycles signifying potential of the porous structure for long-term use under humid conditions. Aqueous-phase sensing studies illustrate extremely specific and ultrafast detection of explosive 246-trinitrophenol (TNP) via remarkable fluorescence quenching (K-SV = 1.3 x 10 (5) M-1) with a 0.25 ppm limit of detection (LOD). Furthermore 3a serves as unique luminescent probe for highly discriminative and quick responsive detection of three noxious oxo-anions (Cr2O7 (2-) CrO4 (2-) MnO4-) in water via noteworthy turn-off responses and extreme low LODs (Cr2O7 (2-) 0.9; CrO4 (2-) 0.29; MnO4- 0.25 ppm). It is imperative to stress the outstanding reusability of the MOF toward multicyclic sensing of all four major water contaminants alongside visible colorimetric changes upon individual analyte detection. Mechanistic insights in light of the electron transfer route together with density functional theory calculations portray the influence of pore functionalization in framework-analyte interactions including alternation in energy levels where varying degrees of contribution of energy transfer explicitly authenticates high quenching of the material.
Keywords: chemically robust cationic MOF; DFT calculation; fast responsive detection; humid CO2 capture; TNP and oxo-anion sensing

Dual-catalyst engineered porous organic framework for visible-light triggered, metal-free and aerobic sp(3) C-H activation in highly synergistic and recyclable fashion - Kumar, Gaurav; Dash, Soumya Ranjan; Neogi, Subhadip (Journal of Catalysis, 2021)
Photoredox and organo-catalysis denote powerful construction tools for new classes of carbon-carbon bonds, where incisive amalgamation of both the approaches over a single, recyclable platform can bring about synergic and eco-friendly reactions under mild conditions. Aiming at enamine-based photoredox catalysis for atom-economic and metal-free sp(3 )C-H activation, an amide-based two-dimensional (2D) porous organic framework (POF) is devised. The pendent -NH2 groups are judiciously anchored with two catalytic stations viz. Rose Bengal and L-proline, through stepwise variation of solid phase peptide synthesis. The dual-catalyst engineered POF represents a fully organic material that synergistically performs visible-light triggered oxidative Mannich reaction to produce biorelevant heterocycle beta-amino ketone in excellent yield at room temperature, using oxygen as clean and selective oxidant. Importantly, activity of this bi-functionalized catalyst compares favorably well to individual homogeneous counterparts. The covalently modified framework demonstrates economic viability via gram-scale synthesis besides admirable reusability, and proves to be effective for nineteen varieties of substrates. The photocatalytic path is detailed from efficient energy transfer from host polymer to substrate in light of experimental and theoretical studies, which provides proof-of-concept to the photo-organo combined mechanism. The material benefits heterogenising two homogeneous catalysts, besides excluding additional steps of conventional Mannich reactions, and offers a step-forward to smart and green cross-dehydrogenative coupling reactions. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Atom-economy; C-H activation; Dual-catalyst engineering; Metal-free reaction; Photo-organo catalysis; Porous organic framework

Direct (hetero)arylation (DHAP) polymerization of conjugated polymers - new A-B-A monomer design for P(NDI2OD-T2) & the challenges of adopting DHAP for continuous flow processes - Kakde, Navnath R.; Bharathkumar, H. J.; Wavhal, Bhaiyyasaheb A.; Nikam, Arun; Patil, Suneha; Dash, Soumya Ranjan; Vanka, Kumar; Krishnamoorthy, K.; Kulkarni, Amol; Asha, S. K. (Journal of Materials Chemistry C, 2022)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, was synthesized by the atom-economic direct hetero arylation polymerization (DHAP) route using a newly designed A-B-A monomer. The new monomer design involved flanking naphthalene diimide with bithiophene units in the bay position, which was further polymerized with bay substituted 1,4-dibromo naphthalene diimide, to afford the same polymer structure as P(NDI2OD-T2). The new monomer design resulted in a very high molecular weight (M-n: 99.5 kDa, D-M: 2.8) defect-free polymer in a quantitative yield by the DHAP batch process using 1,2,4-trichlorobenzene (TCB) as the solvent. DFT studies revealed that the abstraction of the alpha-proton from the naphthalene diimide substituted 2,2 `-bithiophene was favorable by 2.6 kcal mol(-1) (Delta Delta G) as compared to that from 2,2 `-bithiophene. The reason for this improved C-H activation at the alpha position can be attributed to the presence of C-HMIDLINE HORIZONTAL ELLIPSIS pi stabilizing interactions in naphthalene diimide substituted 2,2 `-bithiophene, which strengthens upon the extended charge delocalization throughout the ring, thus stabilizing the conjugate base generated after the proton abstraction. Continuous flow polymerization was carried out by pumping the DHAP reaction mixture including the monomers, catalyst, and additive (pivalic acid) solubilized in degassed TCB through a pre-heated glass condenser packed with K2CO3 and Celite under aerobic conditions. Reproducible molecular weights of M-n: 29.5 kDa, D-M: 1.7 were obtained at much lower concentrations of reactant mixture compared to that for batch polymerization. This is the first report of the synthesis of P(NDI2OD-T2) by a Continuous Flow Process adopting the DHAP route to obtain a defect-free polymer with reasonable molecular weights. P(NDI2OD-T2) was also synthesized by Stille polymerization as a reference control sample to compare the thermal and charge carrier transport properties of the DHAP polymers. Organic field-effect (OFET) mobility measurements indicated mobility values in the order of 10(-3) cm(2) V-1 s(-1) for the DHAP batch polymer (using the novel monomer design). The P(NDI2OD-T2) synthesized by DHAP batch using the commonly used starting materials - bisbromo naphthalene diimide and bithiophene, exhibited OFET mobilities which were one order less, similar to 10(-4) cm(2) V-1 s(-1). This observation highlights the importance of structural design in the monomer to enhance reactivity and thereby the bulk properties using the DHAP route.